In-office dental bleaching in adolescents using 6% hydrogen peroxide with different application tips: randomized clinical trial - Taynara de Souza CARNEIRO; Michael Willian FAVORETO; Michel Wendlinger Cantanhede FERREIRA; Laís Giacomini BERNARDI; Heloísa Forville de ANDRADE; Matheus Coelho BANDECA; Alessandra REIS; Laura CEBALLOS GARCÍA; Alessandro Dourado LOGUERCIO (Journal of Applied Oral Science, 2023)
Abstract Despite the availability of in-office bleaching gels with a 6% concentration of hydrogen peroxide (HP), these gels have not been evaluated in younger patients. They are commercially available with a tip, associated or not with a brush, where the tip with a brush spreads the gel over the entire surface to have a smaller thickness (thin layer) since the manufacturers indicate the application of a thin layer of gel. Objective This randomized, split-mouth, double-blind clinical trial evaluated the efficacy of in-office bleaching with 6% HP in adolescents using different application tips, as well tooth sensitivity (TS) and aesthetic self-perception. Methodology Sixty participants were randomized for 6% HP self-mixing bleaching gel tip design: without brush and with brush. In-office bleaching was performed in 3 sessions of 50 minutes. Color change was evaluated using a digital spectrophotometer (ΔE ab , ΔE 00 , and ΔWI D ) and color guide (ΔSGU), the absolute risk and intensity of TS with a visual analogue scale and aesthetic self-perception with the oral aesthetic scale (a=0.05). Results The groups achieved similar bleaching regardless of the application tip (p>0.05). However, only for ΔWI D , a significant mean difference (MD) was observed in the third week (MD 2.3; 95% CI 1.2 to 3.3; p < 0.001) and at one month (MD 1.6; 95% CI 0.6 to 2.6; p < 0.03) favoring the tip without brush. Regarding TS, 45% in the tip-without-brush group and 33% in the tip-with-brush group reported TS (odds ratio 0.61; 95% CI 0.29 to 1.28; p<0.02), with low TS intensity (MD 0.05; 95% CI -0.06 to 0.17; p>0.36). All patients reported improved aesthetic self-perception after bleaching (MD -1.3; 95% -1.8 to -0.9; p<0.001). Conclusions Regardless of the tip used bleaching with 6% HP achieved a bleaching efficacy and improved the aesthetic self-perception. However, a lower risk of TS for application using the tip with brush was observed.